Evaluating Sharia Compliance in Virtual Office Business Models: A Case Study of BMS Office - Hero Gefthi Firnando; Cucu Setiawati (UIN Raden Mas Said Surakarta, 2026)
The rapid growth of virtual office services has transformed contemporary business practices by providing flexible and cost-efficient alternatives to conventional office spaces. However, previous studies have predominantly examined virtual office models from managerial, operational, and economic perspectives, while limited attention has been given to their compliance with Islamic Business Management principles. This study addresses this gap by evaluating the virtual office business model implemented at BMS Office through the lens of Islamic Business Management and Sharia compliance. The novelty of this research lies in integrating the analysis of virtual office business practices with an Islamic ethical evaluation framework based on the principles of amanah (trustworthiness), adl (justice), sidq (honesty), gharar (avoidance of uncertainty), and mas’uliyyah (responsibility). A qualitative case study approach was employed, with data collected through in-depth interviews, direct observations, and document analysis. The findings reveal that the virtual office business model at BMS Office demonstrates a moderate-to-high level of Sharia compliance. Strong compliance is evident in the principles of sidq and responsibility through transparent contractual arrangements, clear service information, regulatory adherence, and client verification procedures. Meanwhile, the principles of amanah, adl, and gharar show moderate-to-high compliance, although improvements are still needed in service monitoring, communication consistency, documentation clarity, and supervision of address utilization. The study concludes that virtual office services can align with Islamic Business Management principles when supported by transparent contracts, ethical governance, and effective monitoring systems. Practically, the findings provide guidance for virtual office providers in developing more transparent, accountable, and Sharia-compliant business practices.